Arctic Social Indicators - A follow-up to the Arctic Human Development Report - Larsen, Joan Nymand Ed. (Nordic Council of Ministers, 2010)
This report is a result of and follow-up to the Arctic Human Development Report (AHDR), which appeared in 2004. While the first thoughts regarding Arctic Social Indicators (ASI) project reach back to the years 2004 and 2005, the majority of work for the initiative was produced during the years 2006-2009.